Family Guy: Season 1 disc 2 - Seth MacFarlane; Borstein, Alex, 1971-; Mila Kunis; Seth Green; Seth MacFarlane (USA 20th Century Fox Television, 1999)
The Griffin household includes two teenagers, a cynical dog who is smarter than everyone else, and a mutant baby who makes numerous attempts to eradicate his parents and siblings. Heading up this eclectic household is Peter Griffin. Peter does his best to do what's right for the family, but along the way, he makes mistakes that are the stuff of legends.
In a wacky Rhode Island town, a dysfunctional family strive to cope with everyday life as they are thrown from one crazy scenario to another.
Language: English Subtitle: English
Keywords: Comedy; Animation -- Tv Series